Usage of business simulation games in Croatia - Zoroja, Jovana (Managing global transitions, 2013)
Business simulation games (BSGS) enhance learning, since they actively involve students in the educational process through game playing. They began to play important role in business education in many universities in Croatia. However, quantitative information on their usage in higher educational institutions (HEIS) in Croatia is still scarce. Goals of the paper are to explore: (1) differences among BSGS users and non-users according to demographic characteristics, (2) differences among BSGS users and non-users according to perceived obstacles of BSGS usage, and (3) impact of both demographic characteristics and perceived obstacles on the decision on usage or not-usage of BSGS. A survey was taken in business and economics departments of HEIS in Croatia. A regression model has been used to test the impact of demographic characteristics of educators and the perceived obstacles to the usage of BSGS in educational practice. Results indicate that BSGS usage is currently at a low level, mainly due to the lack of funds and management support. Academic rank, gender, and attitude toward new technologies also impact BSGS usage.
Keywords: business economics education; poslovno izobraževanje; simulacijske igre; business simulation games; ovire; perceived obstacles